2014
DOI: 10.1039/c4ra10417j
|View full text |Cite
|
Sign up to set email alerts
|

New insight into the shape-controlled synthesis and microwave shielding properties of iron oxide covered with reduced graphene oxide

Abstract: We proposed various approaches for the shape-controlled synthesis of iron oxide-RGO composites to evaluate the effect of different morphologies on their microwave shielding properties. The nature of various ferrite structures (flakes, cubes and rods) covered by reduced graphene oxide multilayers has been investigated using X-ray diffraction, Raman spectroscopy, FT-IR, scanning electron microscopy, high-resolution transmission electron microscopy and X-ray photoelectron spectroscopic techniques.The electromagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Further, a number of studies on EMI shielding properties of spinel ferrite with graphene have been reported by researchers [13,14,15]. However, there are few studies on EMI shielding properties of nanocomposites consisting of NiFe 2 O 4 spinel ferrite nanoparticles with graphene.…”
Section: Introductionmentioning
confidence: 99%
“…Further, a number of studies on EMI shielding properties of spinel ferrite with graphene have been reported by researchers [13,14,15]. However, there are few studies on EMI shielding properties of nanocomposites consisting of NiFe 2 O 4 spinel ferrite nanoparticles with graphene.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Hybrids composed of iron oxides and graphene also have numerous promising uses. [11][12][13][14] The iron oxides that can be employed in this manner include magnetite (Fe 3 O 4 ), maghemite (g-Fe 2 O 3 ) and hematite (a-Fe 2 O 3 ) ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the imminent increase in the microwave absorption properties of the PPY/0.05 M/ 0.05/T can be related to the both complex and real part of permittivity of nano size of TiO 2 particles. Due to the small size, the anisotropic energy of the particles will be high and the increased anisotropy energy contributes to the enhancement of microwave absorption [15]. Besides the small size of TiO 2 particles, the efficient decoration of TiO 2 particles on MLG sheets lead to the increased polarization charges on the surface.…”
Section: Resultsmentioning
confidence: 99%